2000
DOI: 10.1023/a:1008992911775
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Polyethylene, metal, and ceramics particles have different individual isolation protocols, as shown in Table 1. Nevertheless the reported common steps of particle isolation protocol are categorized into three different stages [87105]: (Step 1) sample delipidation and tissue digestion; (Step 2) dilution, centrifugation, and protein separation and (Step 3) ultrasonication and debris separation. These steps are summarized from a regular chain of a continuous isolation process and are illustrated as a flowchart (Figure 2).…”
Section: Wear Debris Isolation Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene, metal, and ceramics particles have different individual isolation protocols, as shown in Table 1. Nevertheless the reported common steps of particle isolation protocol are categorized into three different stages [87105]: (Step 1) sample delipidation and tissue digestion; (Step 2) dilution, centrifugation, and protein separation and (Step 3) ultrasonication and debris separation. These steps are summarized from a regular chain of a continuous isolation process and are illustrated as a flowchart (Figure 2).…”
Section: Wear Debris Isolation Protocolmentioning
confidence: 99%
“…The results showed good correlation with the radiographic appearance and indicated that extended tissue damage in a particular zone around the total joint that was proportional to the volume of the wear debris in that zone. Another extraction method of analysis is laser diffraction particle analysis [87], which has advantages in retaining the particles in the solution produced by the purification technique that avoids agglomeration and contamination [123]. Three-dimensional imaging approaches for particle quantification were reported in several studies [34,109,125,126].…”
Section: Debris Characterizationmentioning
confidence: 99%
“…The wear particles in the lubricant are satisfied some inherent distribution [6][7][8][9][10][11]. And wear debris size distribution usually meets the two parameters Weibull distribution function [9][10][11].…”
Section: Materials Engineering and Automatic Control IImentioning
confidence: 99%